Pengaruh Variasi Konsentrasi Larutan Pembersih Lantai Terhadap Pencapaian Standar Baku Mutu Kepadatan Kuman di IGD RSUD PANDEGA Kabupaten Pangandaran - hari, Munto (Medical : Jurnal Kesehatan dan Kedokteran, 2024)
The use of disinfectants to clean floors in hospital patient care areas is an effort carried out routinely to ensure environmental quality meets predetermined requirements. Floor cleaning for the period July-December 2023 in the Emergency Room (IGD) of the Regional General Hospital (RSUD) "Pandega" Pangandaran Regency using MiLL 21 disinfectant with a composition of 1 part MiLL 21 liquid to 50 parts water (product standard), the results are floor germ numbers amounting to 20 cfu/cm2, does not meet the floor germ standard based on the Republic of Indonesia Minister of Health Regulation Number 7 of 2019 of 0-5 cfu/cm2. Therefore, it is necessary to experiment using the concentration of MiLL 21 solution to obtain a more effective concentration level as a germ killer. This study aims to analyze the effect of variations in the concentration of floor cleaning solutions on achieving germ density quality standards on the floors of the Emergency Room (IGD) of the Regional General Hospital (RSUD) "Pandega" Pangandaran Regency, West Java Province. The type of research used was an experiment with a completely randomized design for each treatment, the population was a floor area of 200 m2 and the sample was 33 m2 taken using random sampling techniques. The results show that variations in MiLL 21 concentration of 5% are effective in achieving the quality standard limit for floor germ density with sig 0.000>0.05 (α). Suggestions for those responsible for cleaning floors to use variations in the concentration of MiLL 21 floor cleaning solution, at least in a ratio of 1 part solution to 20 parts water, to effectively achieve the specified floor germ density quality standards.